"Corporate Purpose" as a False Friend: A Bibliometric Analysis - Siems, Mathias (Victoria University of Wellington Law Review, 2025)
The term "corporate purpose" is frequently used, both in academic and non-academic writings today. However, it is also quite ambiguous, particularly in relation to the precise obligations that companies may be expected to fulfil. By presenting a bibliometric analysis of this term over recent decades, this article assesses its popularity and usage. It finds that the term "corporate purpose" was already quite popular in the 1960s and 1980s, yet with different meanings than today; that recent publications discuss this term in more detail than in the past; that it is today often associated with social and environmental topics; and that it has recently become a term frequently used in the management and business literature. Overall, the empirical findings of this article confirm that while the term has many ambiguities, and thus may not be a useful legal term, it may well be suitable as a conceptual framing device for the importance of social and environmental interests related to companies.